Significant features for steganography techniques using deoxyribonucleic acid: a review - Nichirvan Asaad Zebari; Dilovan Asaad Zebari; Diyar Qader Zeebaree; Jwan Najeeb Saeed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Information security and confidentiality are the prime concern of any type of communication. Rapidly evolution of technology recently, leads to increase the intruder’s ability and a main challenge to information security. Therefore, utilizing the non-traditional basics for information security is required, such as DNA which is focused as a new aspect to achieve better security. In this paper, a survey of more recent DNA based on data hiding algorithms are covered. With particular emphasis of different parameters several data hiding algorithms based on DNA has been reviewed. To present a more secure an efficient data hiding algorithms based on DNA for future works, this willbe helpful.